2016
DOI: 10.3892/etm.2016.3312
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of perazine ferulate tablets combined with eucalyptol limonene pinene enteric soft capsules for treatment of children with IgA nephropathy

Abstract: The clinical effects of piperazine ferulate tablets combined with eucalyptol limonene pinene enteric soft capsules for treatment of children with IgA nephropathy were investigated. Sixty children with IgA nephropathy were included in the study and were randomly divided into the control (n=30) and observation (n=30) groups. The patients in the control group were treated with conservative or hormone therapy while patients in the observation group were treated with piperazine ferulate tablets combined with eucaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Piperazine ferulate tablets combined with eucalyptol, limonene, and pinene enteric soft capsules were used for IgA nephropathic children therapy by Liu et al [82]. In the observation group, patients were treated with piperazine ferulate tablets (0.1 g/dose and 3 times/day) combined with eucalyptol, limonene, and pinene enteric soft capsules (0.1 g/dose and 2 times/day) for 6 months.…”
Section: Preclinical Pharmacological Activities Of α- and β-Pinenementioning
confidence: 99%
See 1 more Smart Citation
“…Piperazine ferulate tablets combined with eucalyptol, limonene, and pinene enteric soft capsules were used for IgA nephropathic children therapy by Liu et al [82]. In the observation group, patients were treated with piperazine ferulate tablets (0.1 g/dose and 3 times/day) combined with eucalyptol, limonene, and pinene enteric soft capsules (0.1 g/dose and 2 times/day) for 6 months.…”
Section: Preclinical Pharmacological Activities Of α- and β-Pinenementioning
confidence: 99%
“…The effective rate of observational group (12 patients) was significantly higher when compared with hormone group (18 patients). Differences between serum IgA, fibronectin, and complement C3 of two selected groups were not statistically significant [82].…”
Section: Preclinical Pharmacological Activities Of α- and β-Pinenementioning
confidence: 99%
“…Piperazine ferulate (Piperazine 3-methoxy-4-hydroxycinnamate; PF; Fig. 1A ) is a derivative of ferulic acid that exhibits anti-hypertensive effects ( 14 ), reduces IgA-mediated nephropathy ( 15 ) and prevents the development of DN ( 16 ). A systematic meta-analysis indicated that PF combined with irbesartan could improve the efficiency of treatment of DN ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Piperazine ferulate (PF; C 4 H 10 N 2 •2C 10 H 10 O 4 ; 474.51 g/mol; Fig. 1A), a compound synthesized by ferulic acid and piperazine, is used in the treatment of various types of kidney disease including DN, nephritis (20) and immunoglobulin (Ig) A nephropathy (21) in China. Previous research has revealed that PF reduces the levels of blood urea nitrogen and serum creatinine in rats subjected to 5/6 nephrectomy (22) and exerts anti-hypertensive effects via the activation of endothelial nitric oxide synthase (eNOS) (23).…”
Section: Introductionmentioning
confidence: 99%